Modeling Interdependencies between Information Processes and Communication Paths in Hospitals - Brigl, B.; Strübing, A.; Wendt, T.; Winter, A. (Methods of Information in Medicine, 2006)
Objectives: For planning hospital information systems it is important to recognize the interrelation between business processes and the communication needs between supporting application systems. We therefore present an approach to model, visualize and analyze those interdependencies.Methods: The approach is based on the concepts defined in 3LGM2, a meta-model to describe health information systems (HIS). An information process is defined as a sequence of functions using or updating information; a communication path as a sequence of communication links between interfaces belonging to application systems. The search for communication paths belonging to an information process is interpreted as an all-pairs shortest-paths problem. To solve this problem the Floyd-Warshall algorithm is applied.Results: The resulting algorithm has been implemented as function of the 3LGM2 tool, a tool to create 3LGM2 compliant models. With it, it is possible to interactively define information processes at the domain layer and to analyze step by step whether the infrastructure at the logical tool layer is sufficient to communicate necessary data between application systems.Conclusions: The presented approach enables the representation and analysis of dependencies between information processes and communication paths.With it, the HIS architecture is directly associated with the business needs. This is an important condition for the systematic planning of hospital information systems.
Keywords: Hospital information systems; architectural models; process modeling; information processes; communication paths